1988
DOI: 10.1038/hdy.1988.128
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of carbohydrate metabolism and growth in Eisenia foetida (Oligochaeta: Lumbricidae)

Abstract: The heterozygosity of 13 polymorphic loci, encoding 10 enzymes from several pathways in carbohydrate metabolism, was tested for its effect on growth in juvenile manure worms Eisenia foetida (n = 169), raised under stressful (limited food, low moisture) followed by non-stressful (abundant food, high moisture) conditions. The predictive value of heterozygosity on growth was greatly improved by treating each locus separately rather than summing heterozygosity across all loci (multilocus heterozygosity). Under non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…This general expectation has provided the incentive for numerous empirical studies of the relationship between individual heterozygosity, the number of loci from a sample for which an individual is heterozygous (Mitton & Pierce, 1980), and various components of fitness (Zouros et at., 1980;Koehn & Shumway, 1982;Pierce & Mitton, 1982;Garton, 1984;Hawkins et at., 1986Hawkins et at., , 1989Rodhouse et at., 1986;Bush et at., 1987; Danzmann et at., 1987;Diehl, 1988;Koehn et at., 1988;Gajardo & Beardmore, 1989;Ferguson & Drahushchak, 1990;Teska et at., 1990;Mopper et at., 1991;Pecon Slattery et al, 1991). These studies reveal that fitness generally increases with heterozygosity (see reviews by Beardmore, 1983;Mitton & Grant, 1984;Allendorf & Leary, 1986;Ledig, 1986;Zouros & Foltz, 1987;Mitton, 1989Mitton, , 1993.…”
Section: Discussionmentioning
confidence: 99%
“…This general expectation has provided the incentive for numerous empirical studies of the relationship between individual heterozygosity, the number of loci from a sample for which an individual is heterozygous (Mitton & Pierce, 1980), and various components of fitness (Zouros et at., 1980;Koehn & Shumway, 1982;Pierce & Mitton, 1982;Garton, 1984;Hawkins et at., 1986Hawkins et at., , 1989Rodhouse et at., 1986;Bush et at., 1987; Danzmann et at., 1987;Diehl, 1988;Koehn et at., 1988;Gajardo & Beardmore, 1989;Ferguson & Drahushchak, 1990;Teska et at., 1990;Mopper et at., 1991;Pecon Slattery et al, 1991). These studies reveal that fitness generally increases with heterozygosity (see reviews by Beardmore, 1983;Mitton & Grant, 1984;Allendorf & Leary, 1986;Ledig, 1986;Zouros & Foltz, 1987;Mitton, 1989Mitton, , 1993.…”
Section: Discussionmentioning
confidence: 99%
“…For the small worms in treatments 3 and 4, intact worms were homogenized in buffer to which phenylmethylsulfonyl fluoride (0.1 mM) had been added to retard the activity of proteolytic enzymes in the anterior portion of the worm. Homogenates were prepared as in Diehl (1988) were resolved on the Tris-maleate, pH 7.4, buffer system of Selander & Yang (1969). All loci except Aap and Hbd were stained according to Diehi & Williams (1 992a).…”
Section: Methodsmentioning
confidence: 99%
“…In some studies (e.g. Samollow & Soulé, 1983;Diehl & *Correspondence Koehm, 1985), the case that a stressful environment caused MLH-fitness relationships has been made a posteriori. In other studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Pecon Slattery et al (1993) reported a significant relationship between heterozygosity and age class in the hard clam Mercenaria mercenaria, but the relationship was not consistent over a 3-year sampling period. Consistency of MLH-fitness relationships has also been lacking from a series of studies on Eisenia andrei (Diehl, 1988;Audo and Diehl, 1995;McElroy et al, 1999;McElroy and Diehl, 2001), although some of this inconsistency disappears when a common set of loci are used (Audo and Diehl, 1995). In the above studies, inbreeding, migration, selective mortality, and ontogenetic effects may have affected heterozygosity-fitness relationships.…”
Section: Introductionmentioning
confidence: 99%